Description of a new species of Ovaticoccus Kloet (Hemiptera: Coccoidea, Eriococcidae) from Belize, with remarkably large hind coxae and causing leaf-curl galls - Williams, D. J.; Martin, J. H. (Zootaxa, 2003)
A new species of eriococcid scale insect, Ovaticoccus amplicoxae, is described from Belize. The species has enormous hind coxae, unlike any described so far in this genus, or in related genera. In life, the species galls the leaves to such an extent that it has been impossible to identify the host plant.